The evolution of resource management in Taiwanese fisheries: coastal and offshore perspectives - Wu,Yan-Lun; Lim,Irene Chia Ling; Li,LiXliang; Chen,Lu-Chi; Hsiao,Po-Yuan; Lee,Wei-Yu; Lan,Kuo-Wei (PeerJ, 2024)
This study investigates the historical changes in resource development of offshore and coastal fisheries around Taiwan from 1970 to 2021 using the mean trophic level (MTL) and Fishing-in-Balance (FiB) indices. Utilizing data from the Fisheries Statistical Yearbook, three scenarios were employed to assess the effects of highly migratory, oceanic migratory, and seasonal migratory fish species on the MTL and FiB indices. The analysis revealed a continuous increase in MTL for offshore and coastal fisheries, suggesting shifts in the trophic structure and potential over-exploitation of higher trophic level species. The FiB index for offshore fisheries exhibited a declining pattern after 1990, reflecting the depletion of indigenous fish stocks, while the FiB for coastal fisheries showed an increasing trend from 1970 until the 2000s, followed by a decrease, highlighting unsustainable fishing practices. Moreover, the study identified Scomber australasicus, targeted by Taiwanese Purse Seine, as an influential species affecting the resource dynamics of offshore fisheries. The trawling fisheries would also be a crucial issue affecting the indigenous resource dynamics of offshore fisheries in Taiwan. This study identified a fishing-down mechanism within indigenous fishery dynamics. The potential over-exploitation of fish stocks could result in long-term unsustainable practices if left unaddressed. This study advocates for enhanced fisheries management through stricter regulations on fishing gear, continuous monitoring, and adaptive management strategies. These measures are essential for achieving sustainable development goals and conserving marine biodiversity in Taiwan’s waters. By addressing these critical issues, Taiwan can better manage its fisheries resources and promote ecological balance.
Keywords: Mean trophic level; Fishing in balance; Fishery resource dynamic; Fishing-down; Offshore; Coastal